Advertising in new formats and media : current research and implications for marketers - Pelsmacker, Patrick de, 1957- (Emerald Group Publishing Limited, 2016)
The advertising universe is changing rapidly. New communication technologies such as live streaming, gaming, social media and social networking sites, online brand communities and blogs have given advertisers new platforms to communicate and promote their messages. Two remarkable phenomena are apparent: interactivity in online communication; and integration of editorial and commercial content - or the combination of both of these. Academic research is increasingly focusing upon these new techniques and formats, how they work, and how consumers are affected by or respond to them. This book makes an important contribution to the field of advertising in bringing together state-of-the-art insights into new advertising formats and how they work. Split into three sections: "The Changing Advertising Universe", "Advertising in a Digital Connected World" and "Hidden but Paid for: Branded Content" the book provides conceptual overviews, discusses recent academic literature, reports new research work, and develops viewpoints on the key issues. Together, it provides a valuable overview of insights into modern advertising practice for advertising academics and practitioners alike.- Resumé vydavatel